Survivin and insulin-like growth factor-I: potential role in the pathogenesis of acne and post-acne scar - Samar El-Tahlawi; Noha Ezzat Mohammad; Azza Mohamed El-Amir; Heba Sayed Mohamed (SAGE Publishing, 2019)
Backgrounds/objectives: Acne is an inflammatory disease of the pilosebaceous unit (PSU). The over-expression of survivin and insulin-like growth factor (IGF)-I in some fibrotic disorders suggests a possible implication in the pathogenesis of acne and or post-acne scar. We aimed to evaluate their potential role in pathogenesis in acne and post-acne scar. Methods: Serum survivin and IGF-I levels were estimated in 30 patients with acne and post-acne scar compared to 30 controls. Results: There was a statistically significant difference in survivin and IGF-I levels between controls and patients ( P < 0.05). However, there was no linear correlation between survivin and IGF-I. Conclusions: Survivin and IGF-I could have a possible role in the pathogenesis of active acne and in post-inflammatory acne scar.